(untitled) (Communication & Society, 2011)
This article deals with the use of music in certain specific cinematic genres in the Spanish context. It focuses specifically on two typologies which are very characteristic of the last decade. First, it is possible to trace the existence of a number of comedies which offer second readings of the musical clichés of the adventure genre in order to use them as elements of parody. As a paradigm of this genre, the composer Roque Baños writes in Hollywood symphonic style for the least "cool" productions of Spanish cinema. In contrast, but complementing this, the theme song constitutes a musical trade mark for the latest expressions of the realist genre. These examples show that to the sound trade marks for each genre, standardized musical conventions, we need to add the peculiarities of each country. This gives rise to meanings that arise from the sum of genre clichés and local characteristics.